ELEMENTS OF RAT TESTES UNDER THE INFLUENCE OF INSECTICIDE ROVIKURT - A. T. Dusmatov; S. A. Begmanov; Qodirov Sh. A. (Web of Journals Publishing, 2025)
The purpose of the study was to study the characteristics of the response of germ and somatic cells to the action of rovicurt, as well as to study some aspects of the mechanism of this action.
Keywords: Rovicurt, synaptonemal complex, spermatid, sustentocyte.